Motor unit conduction velocity during sustained contraction after eccentric exercise - Hedayatpour, Nosratollah (2009)
BACKGROUND:Eccentric contractions induce muscle fiber damage that is associated with a decreased capacity to generate voluntary force and increased fiber membrane permeability. Changes in fiber membrane permeability results in cell depolarization that is expected to have an effect on the action potential propagation velocity of the muscle fibers. PURPOSE:The aim of the study was to investigate the action potential propagation velocity in individual motor units before and 24 and 48 h after eccentric exercise. METHODS:Multichannel surface and fine-wire intramuscular EMG signals were concurrently recorded from two locations of the right vastus medialis muscle of 10 healthy men during 60-s isometric contractions at 10% and 30% of the maximal force. RESULTS:The maximal force decreased by 26.1 ± 16.1% (P < 0.0001) at 24 h and remained reduced by 23.6 ± 14.5% (P < 0.0001) 48 h after exercise with respect to baseline. With respect to baseline, motor unit conduction velocity decreased (P < 0.05) by (average over 24 and 48 h after exercise) 7.7 ± 2.7% (10% maximal voluntary contraction (MVC), proximal), 7.2 ± 2.8% (10% MVC, distal), 8.6 ± 3.8% (30% MVC, proximal), and 6.2 ± 1.5% (30% MVC, distal). Moreover, motor unit conduction velocity decreased over time during the sustained contractions at faster rates when assessed 24 and 48 h after exercise with respect to baseline for both contraction forces and locations (P < 0.05). CONCLUSIONS:These results indicate that the electrophysiological membrane properties of muscle fibers are altered by exercise-induced muscle fiber damage.